Existence of new rock unit of pink dolomite within the Midland succession of Balanch area, Darchula, Far-Western Nepal - Sah, Ram Bahadur; Pathak, Dilendra Raj; Paudyal, Kabi Raj (Journal of Nepal Geological Society, 2018)
Geological setting and lithostratigraphy of Balanch area in the Darchula District, Far-western Nepal has been worked out with the aim to study the stratigraphy of the area. It has been found that the Bitule Dolomite developed in this area possibly represents the youngest rock unit of the Midland Group of the Nepal Lesser Himalaya. The Balanch area lies within the autochthonous zone of the Lesser Himalaya. The rock succession has been divided into six units: Bagadi Slate, Simar Talc Beds, Baril Dolomite, Tupkan Slate, Bitule Dolomite, and Balligad Sandstone. The Balligad Sandstone possibly belongs to the rock succession of Lower Tertiary whereas all other units belong to the Midland Group. From south to north, the area is characterized by the development of three tectonic zones. The southern zone is characterized by the development of oldest rock unit (Bagadi Slate) having NW to NE trend and dipping towards south and possibly thrusted over the middle zone. The middle zone is characterized by the development of the Simar Talc Beds, Baril Dolomite, and the Tupkan Slate, and also thrusted over rock succession of the northern zone, which is characterized by the development of the Bitule Dolomite and the Balligad Sandstone, the youngest rock units of the area. Geological setting and lithostratigraphy of Balanch area in the Darchula District, Far-western Nepal has been worked out with the aim to study the stratigraphy of the area. It has been found that the Bitule Dolomite developed in this area possibly represents the youngest rock unit of the Midland Group of the Nepal Lesser Himalaya. The Balanch area lies within the autochthonous zone of the Lesser Himalaya. The rock succession has been divided into six units: Bagadi Slate, Simar Talc Beds, Baril Dolomite, Tupkan Slate, Bitule Dolomite, and Balligad Sandstone. The Balligad Sandstone possibly belongs to the rock succession of Lower Tertiary whereas all other units belong to the Midland Group. From south to north, the area is characterized by the development of three tectonic zones. The southern zone is characterized by the development of oldest rock unit (Bagadi Slate) having NW to NE trend and dipping towards south and possibly thrusted over the middle zone. The middle zone is characterized by the development of the Simar Talc Beds, Baril Dolomite, and the Tupkan Slate, and also thrusted over rock succession of the northern zone, which is characterized by the development of the Bitule Dolomite and the Balligad Sandstone, the youngest rock units of the area.